ANALISIS PENGARUH STRES KERJA, MOTIVASI KERJA DAN PRESTASI KERJA TERHADAP KINERJA - Saputri Ceri Nirmala Insani; Andi Kartika (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to examine the relationships among work stress, work motivation, work performance, and employee performance at PT Wizzmie Boga Abadi Cirebon.I used all 100 employees at PT Wizzmie Boga Abadi Cirebon as the population for my research.Methods: My research used a census method (total sample) with 100 respondents from the entire population. The data analysis I conducted used multiple linear regression.Results: The data analysis I obtained from the research indicates that work stress does not affect employee performance. However, work motivation together with work performance has a significant impact on employee performance at PT Wizzmie Boga Abadi Cirebon. From the study’s findings, we can understand the importance of internal management and the factors that influence employee performance at PT Wizzmie Boga Abadi Cirebon. Recommendations for the Company: Although work stress does not significantly impact employee performance at PT Wizzmie Boga Abadi Cirebon, it is recommended that stress be managed to prevent it from becoming a long-term problem. PT Wizzmie Boga Abadi Cirebon can implement several work-life balance programs, provide counseling facilities, and foster a positive communication environment between employees and superiors. To increase motivation and work performance, the company is recommended to provide performance-based rewards, provide career development opportunities, and establish a transparent and fair evaluation system. Furthermore, team-building activities, regular training, and rewards such as bonuses and public recognition can strengthen employee morale. Creating a supportive and appreciation-oriented work environment at PT Wizzmie Boga Abadi Cirebon has the potential to create employees who are not only high performers but also loyal. Keywords: Employee Performance, Work Achievement, Work Motivation, Work Stress